1982
DOI: 10.1007/bf01869964
|View full text |Cite
|
Sign up to set email alerts
|

Calcium uptake into acini from rat pancreas: Evidence for intracellular ATP-dependent calcium sequestration

Abstract: Intracellular ATP-dependent Ca2+-sequestration mechanisms were studied in isolated dispersed rat pancreatic acini following treatment with saponin or digitonin to disrupt their plasma membranes. In the presence of 45Ca2+ concentrations less than 10(-6) mol/liter, addition of 5 mmol/liter ATP caused a rapid increase in 45Ca2+ uptake exceeding the control by fivefold. ADP mimicked the ATP effect by 50 to 60%, whereas other nucleotides such as AMP-PNP, AMP-PCP, CTP, UTP, ITP, GTP, cAMP and cGMP did not. Maximal A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…Since the plasma membrane of the cells was permeabilized by exposure to the ergosterol-binding antifungal drug, nystatin, the non-vacuolar Ca2 + uptake activity does not originate from the plasma membrane. Neither does the Ca2+ uptake activity originate from the mitochondria, since it was measured in the presence of CCCP, an uncoupler of oxidative phosphorylation and a strong inhibitor of mitochondrial Ca2+ uptake [27]. In addition, it has been found that in yeast, Ca2+ is not taken up into the mitochondria [26].…”
Section: Discussionmentioning
confidence: 99%
“…Since the plasma membrane of the cells was permeabilized by exposure to the ergosterol-binding antifungal drug, nystatin, the non-vacuolar Ca2 + uptake activity does not originate from the plasma membrane. Neither does the Ca2+ uptake activity originate from the mitochondria, since it was measured in the presence of CCCP, an uncoupler of oxidative phosphorylation and a strong inhibitor of mitochondrial Ca2+ uptake [27]. In addition, it has been found that in yeast, Ca2+ is not taken up into the mitochondria [26].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets were suspended in a Krebs-Ringer's-HEPES buffer (120 mM NaC1, 4.7 mM KCl, 1.2 mM KH2P04, 1.2 mM MgC12, 10 mM HEPES, 15 mM dextrose, 0.2% albumin) pH 7.4 (13), for the study of all agonists except IP3. For agonists other than IP3, 1 mM CaC12 was added to each sample 2 min before the addition of agonist.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated changes in Ca ionomycin, which dissipates the extra/intracellular calcium gradient (26,27). Under these conditions, increasing concentrations of Ca 2þ o still caused a concentration-dependent increment of PTHrP production (Fig.…”
Section: Ca 2þ I and Pthrp Productionmentioning
confidence: 99%